2019
DOI: 10.1103/physrevb.100.245429
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic spin-orbit coupling and spin relaxation in phosphorene

Abstract: An effective Hamiltonian is derived to describe the conduction band of monolayer black phosphorus (phosphorene) in the presence of spin-orbit coupling and external electric field. Envelope function approximation along with symmetry arguments are utilized to derive extrinsic spin-orbit splitting, which is shown to be linear in both the magnitude of the external electric field and the strength of the atomic spin-orbit coupling. The spin splitting is akin to the Bychkov-Rashba expression but demonstrates an in-pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…This work 0.14 1.23 −0.13 5.36 [44] 0.17 1.26 −0.16 5.50 [45] 0.16 1.13 -- [46] 0.15 1.24 −0.14 5.92…”
Section: Effective Mass Calculationsunclassified
“…This work 0.14 1.23 −0.13 5.36 [44] 0.17 1.26 −0.16 5.50 [45] 0.16 1.13 -- [46] 0.15 1.24 −0.14 5.92…”
Section: Effective Mass Calculationsunclassified
“…However, since the spin-orbit coupling is expected to be quite small in this system 42 , the sidejump contribution is also unlikely to dominate the large AHE. Moreover, these contributions are expected to scale with M, which is incompatible with the unconventional M dependence that turns on at M ~ MC.…”
mentioning
confidence: 94%
“…Interesting electronic properties such as thermal transport [14][15][16], magnetotransport [17,18], anisotropic in-plane thermal transport [19], electronic band structure [20][21][22][23], particle-hole excitations [13,24], optical properties [25,26], electronic transport [27], charge and spin transport [28] have been investigated in phosphorene. Moreover, interesting effects induced by SOI in phosphorene have been reported [29][30][31][32]. It has been shown that inversion symmetry broken BP exhibits very interesting transport properties [33], where the strong anisotropy in the energy band structure along the two crystal directions leads to linear transverse neutral topological currents, accompanied by nonlinear transverse charge currents at the Fermi surface.…”
Section: Introductionmentioning
confidence: 99%